Effect of pindolol on the prolactin response to d-fenfluramine. - Park, S; Cowen, P (1995)
We studied the effect of the 5-HT1A receptor antagonist, pindolol, on the prolactin (PRL) response to the 5-HT releasing agent, d-fenfluramine (d-FEN), in ten healthy male volunteers. Pindolol pretreatment lowered baseline PRL levels but, when this effect was taken into account, did not significantly attenuate the PRL response to d-FEN. Within the limitations that attend the use of pindolol as a 5-HT1A receptor antagonist, the data suggest that although 5-HT1A receptors may play a role in the tonic release of PRL, they are not involved in the release of PRL produced by d-FEN. We propose that the PRL response to d-FEN may involve selective activation of postsynaptic 5-HT2 receptors.